CAN UMKM IN THE CULINARY SECTOR IN PALEMBANG IMPLEMENT THE SAK ETAP? - Veronika, Aries; Ekawarti, Yuni; Apriadi, Apriadi (BIMA Journal (Business, Management, & Accounting Journal), 2022)
The preparation of financial reports is an important thing that must be done by MSMEs if they want to develop their business, but many MSMEs, especially in the city of Palembang, do not yet have financial reports that comply with SAK standards. The purpose of this study was to determine the application of SAK ETAP on MSME financial reporting in the city of Palembang. The research methodology uses primary data through questionnaires. Based on the results of data processing, it can be concluded that 90% of MSME actors in the city of Palembang have not implemented SAK ETAP in their financial reporting.